2009
DOI: 10.1136/sti.2008.033324
|View full text |Cite
|
Sign up to set email alerts
|

Age at first sex in rural South Africa

Abstract: Objectives: To identify factors associated with sexual debut and early age at first sex (AFS) among young men and women (12-25 years) in a population with a high prevalence and incidence of HIV in rural South Africa. Methods: Longitudinal data from four rounds (2003-7) of a prospective population-based HIV and sexual behaviour survey in rural KwaZulu-Natal were used to investigate the distribution and predictors of earlier first sex. Survival analyses were used, and each analysis considered men and women separ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
65
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(75 citation statements)
references
References 35 publications
10
65
0
Order By: Relevance
“…families with both biological parents) reported later median age of first intercourse than youth living in any other family situation, including stepfamilies with two parents in the home. In a South African study, McGrath et al (2009) found that the hazard of first sex was statistically significantly higher for women and men whose mother or father had died, while on the other hand they found that the hazard of first sex was statistically significantly lower for women whose mother or father was a co-member of the same household.…”
Section: Literature Reviewmentioning
confidence: 99%
“…families with both biological parents) reported later median age of first intercourse than youth living in any other family situation, including stepfamilies with two parents in the home. In a South African study, McGrath et al (2009) found that the hazard of first sex was statistically significantly higher for women and men whose mother or father had died, while on the other hand they found that the hazard of first sex was statistically significantly lower for women whose mother or father was a co-member of the same household.…”
Section: Literature Reviewmentioning
confidence: 99%
“…7 Sexual risky behaviours of unprotected sexual activity may increase the risk of unwanted pregnancy, HIV infection and other sexually transmitted infections (STIs) among young people. [8][9][10][11] The impact of HIV and AIDS, and underage pregnancy on aspects of population in a country are profound. People living with HIV and AIDS are more susceptible to developing opportunistic infections, increasing mortality rates among those affected, and reducing life expectancy.…”
Section: Introductionmentioning
confidence: 99%
“…A Chinese study (Xiao et al, 2010), showed that using alcohol diminished the likelihood of participants using condoms. In a South African study by McGrath et al, 2009, it was observed that for men, age at first sex was associated with having ever used alcohol (OR 1.89, CI 1.55-2.30, p<0.001). …”
Section: Emerging Adultsmentioning
confidence: 99%
“…This sample does not report the highest condom use . In a large sample of 4,724 young women and 4029 young men (12-25 years), having ever used alcohol was significantly associated with a lower age of first sex for both men and women (McGrath et al, 2009). In a study on 661 grade 9 students, alcohol and HIV prevention education affected HIV-related risk factors (Karnell et al, 2006).…”
Section: Outside Of the United Statesmentioning
confidence: 99%